Effects of dimethyl ether addition on soot formation, evolution and characteristics in flame-wall interactions. (1st December 2018) - Luo, Minye; Liu, Dong
Abstract: In this study, the detailed effects of different levels of DME addition on soot formation, evolution and characteristics in flame-wall interactions are studied to improve the energy efficiency and develop soot reduction strategies. A quartz plate which is cooled by the circulating water is uprightly installed above the ethylene jet diffusion flames to generate the flame-wall interactions. The impinging flame propagates along the surface and a series of soot rings are formed. Soot particles from different regions which represent various combustion stages are sampled and analyzed. The nanostructure of soot is acquired by the high resolution transmission electron spectroscopy (HRTEM). The results of Raman spectroscopy reflect the soot graphitization degree and verify the HRTEM findings. The thermogravimetric analyzer (TGA) is adopted to evaluate the oxidation reactivity of soot particles. The results show that the flame impingement exhibits a significant impact on soot evolution and characteristics. The addition of DME performs well in suppressing soot formation and promoting energy efficiency. The addition of 20% DME suppresses the production of soot particles from post-impingement regions and promotes the oxidation reactivity. However, the promotion of soot formation and the reduction of oxidation reactivity are found in post-impingement regions with 5% DME addition. Highlights: Effects of DME addition on soot formation in flame-wall interactions were studied. Soot at initially impingement region has amorphous structures. Soot from out-flame region shows a typical core-shell nanostructure. The reactivity of soot decreased with 5% DME addition. Soot reactivity of post-impingement regions increased with 20% DME addition.